2017
DOI: 10.3389/fphys.2017.00281
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Chicken Skeletal Muscle during Embryonic Development

Abstract: Embryonic growth and development of skeletal muscle is a major determinant of muscle mass, and has a significant effect on meat production in chicken. To assess the protein expression profiles during embryonic skeletal muscle development, we performed a proteomics analysis using isobaric tags for relative and absolute quantification (iTRAQ) in leg muscle tissues of female Xinghua chicken at embryonic age (E) 11, E16, and 1-day post hatch (D1). We identified 3,240 proteins in chicken embryonic muscle and 491 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…The results alone suggest that embryonic skeletal muscles express higher TPM3α transcripts than the 15‐day post‐hatch animals and still higher than muscles from adult chicken. Our finding on the expression of TPM3a transcripts in embryonic chicken skeletal muscles is in agreement with the findings of Ouyang et al (). These authors performed proteomic analysis of chicken skeletal muscle during embryonic development and found the elevated amount of TPM3 expression in embryonic (E11) vs. D1 or developed chicken.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results alone suggest that embryonic skeletal muscles express higher TPM3α transcripts than the 15‐day post‐hatch animals and still higher than muscles from adult chicken. Our finding on the expression of TPM3a transcripts in embryonic chicken skeletal muscles is in agreement with the findings of Ouyang et al (). These authors performed proteomic analysis of chicken skeletal muscle during embryonic development and found the elevated amount of TPM3 expression in embryonic (E11) vs. D1 or developed chicken.…”
Section: Discussionsupporting
confidence: 94%
“…Sarcomeric TPM3 isoform has long been known to play a critical role in muscle contraction in slow skeletal muscle in vertebrates. However, no sarcomeric TPM3 protein or its cDNA clone has been reported until June 3, 2017 (variant 4; NM_001352041.1) (Ouyang et al, 2017), while we were submitting our TPM3a sequence in GenBank (submission id: MF347378). Interestingly, the nucleotide as well as deduced amino acid sequences of a low molecular weight TPM3 isoform (TPM3b) was reported by MacLeod (1982) .…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that the adjuvant properties of SO-VE-GS may be attributed to activation of immune-related genes and pathways [32]. This proteomic technology [56] is based on isotopic labeling and has been applied in several aspects, including production mechanisms [57], growth performance [44], and disease resistance of animals [58][59][60]. However, few studies have looked at its use in vaccine adjuvant research.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the protein-protein interaction networks, STRING software [44] was adopted. In the SO-VE-GS vs. control comparison, 23 differentially expressed proteins were analyzed and 16 of them constituted an interaction network with 23 nodes and 23 edges.…”
Section: Interaction Network Of Depsmentioning
confidence: 99%
“…The embryonic phase is important for skeletal muscle development and growth 18 . During this phase, the muscle fibres are formed and proliferated at early embryonic stage and hypertrophic at late stage 19,20 , which has great influence on production of meat mass 21 .…”
Section: Discussionmentioning
confidence: 99%